Peran Tasawuf Dalam Meningkatkan Ketahanan Psikologis Pengusaha Muda - Nabila Nurrizki Awalia Effendi; Dicky Tri Prayoga (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research aims to examine the application of Sufism principles in a business context and its influence on mental resilience and business success. The method used in this research is a qualitative approach with purposive sampling techniques and snowball sampling with subjects aged between 21-30 years who are entrepreneurs. Data was collected through in-depth interviews with several entrepreneurs who apply Sufism in their business activities. The research results show that the principles of Sufism such as patience, trust, sincerity and gratitude have a significant role in helping entrepreneurs overcome business pressures and challenges. Entrepreneurs who apply Sufism principles are proven to have lower stress levels, higher motivation, and a better ability to make wise decisions. Apart from that, the application of Sufism also has a positive impact on the balance between material and spiritual aspects, creating more holistic and meaningful business success. This research makes an important contribution to understanding how the integration of spiritual values in business practices can improve entrepreneurs' mental well-being and drive sustainable success.